Phylogeography and population genetics of Acanthophyllum squarrosum complex (Caryophyllaceae) in the Irano-Turanian region. Issue 4 (19th May 2019) - Mahmoudi Shamsabad, Masoumeh; Assadi, Mostafa; Parducci, Laura
Abstract : Acanthophyllum squarrosum and two closely related species, A. heratense and A. laxiusculum (Caryophyllaceae), form a complex that covers parts of subalpine steppes of the Irano-Turanian (IT) region. In this study, we explored the genetic structure and phylogeography of this complex based on partial sequences of two chloroplasts ( psb A– trn H and rpl 32– trn L (UAG)) and two nuclear (EST24 and nrITS) DNA regions. We analysed 80 individuals from eight populations and detected 12 chloroplast haplotypes, 16 and eight nuclear alleles in EST24 and nrITS sequences, respectively. Phylogenetic trees and haplotype networks did not show distinct genetic groups in the complex and this could be explained by incomplete lineage sorting or introgression between species. Divergence time analysis revealed a Quaternary origin for A. squarrosum complex at approximately 1.8 million years ago (Mya) and the neutrality test results indicated that this complex experienced a recent population expansion. AMOVA analysis of the chloroplast regions showed a significant genetic differentiation among populations and low genetic differentiation within populations, but opposite results were found with nuclear markers, implying introgression between A. squarrosum complex populations.